ANTHROPOLOGICAL ANALYSIS OF HUMAN SKELETAL REMAINS IN FORENSIC CASES - Jankova, Renata (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Anthropological analysis of skeletal human remains is an important aspect in determining the identity of the deceased, time of death and eventually the cause and manner of death. Given the fact that bones and teeth survive much longer in comparison to soft tissue, analysis of skeletal and dental characteristics is quite often a material in forensic investigation and is of substantial value in forensic casework. Through interpreting the shape and size of the skeletal remains, four basic biological criteria such as skeletal age, biological sex, living stature and ancestry or racial affiliation could be determined, individualizing the deceased. Describing the unknown human remains in such a way becomes a feasible way to create a biological profile of the individual studied, and to enable law enforcement to narrow the range of possible missing identities. In the investigation of mass graves and identification of victims of mass disasters, forensic anthropology investigation is crucial. In this article, some of the forensic cases of human skeletal remains anthropological investigation in our practice, are presented. A case where through analysis of the morphological and metric characteristics of the skeletal remains, biological sex, age, and stature of the deceased were estimated and a case where with analysis of bone fragments more than one individual present within the remains was determined. These analyses are important in medicolegal aspect. Key words: forensic anthropology, human skeletal remains, biological profile.